Preparation method and application of ammonia adsorption titanium-based metal organic framework material
Low-temperature synthesis of Ti-MOFs with controlled pore size enhances ammonia adsorption, addressing poor performance in existing Ti-MOFs and facilitating their use in deodorization and ammonia storage.
Patent Information
- Application Number
- CN202411350152.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
Titanium-based metal-organic framework materials (Ti-MOFs) exhibit poor ammonia adsorption performance, limiting their application in deodorizing and ammonia storage materials.
A low-temperature solvothermal synthesis method is employed, adjusting the reaction temperature between 68 to 98°C, to produce Ti-MOFs with pores below 10-50nm, enhancing ammonia adsorption capacity.
The method improves ammonia adsorption performance, reduces carbon dioxide emissions, lowers reaction risk, and increases production efficiency, enabling effective use in deodorization filters and ammonia storage and transportation.
Smart Images

Figure CN119219932A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gas adsorption materials, and in particular to a preparation method and application of an ammonia adsorbed titanium-based metal organic framework material. Background Art
[0002] Ammonia is a colorless gas with a pungent odor, and is a common source of odor in industry and animal husbandry. Currently, the use of adsorption materials (such as activated alumina, activated carbon, molecular sieves, etc.) to adsorb ammonia is a commonly used method for removing ammonia.
[0003] Metal-organic framework materials (MOFs) refer to an ordered nanoporous framework material with a periodic network structure formed by organic ligands and transition metal ions linked by coordination bonds. MOFs have the advantages of large specific surface area, special topological structure, controllable pore size, and adjustable functionalization, and are being considered for application in the field of gas adsorption (JP2023519686A). Titanium-based metal-organic framework materials (Ti-MOFs) have attracted widespread attention in gas separation, storage and photocatalytic conversion due to their excellent stability and photoactivity. For example, Chinese patent CN116693866A discloses a titanium-based metal-organic framework material and its preparation method and application, which prepares a titanium-based metal-organic framework material with high porosity and specific surface area, which can be used in the fields of gas adsorption and separation, photoelectrocatalysis, and drug sustained release.
[0004] However, when Ti-MOFs in the prior art are used for gas adsorption, their adsorption performance for ammonia is poor, which is not conducive to their application in deodorizing materials. Summary of the invention
[0005] The present invention aims to overcome the problem of poor ammonia adsorption performance of titanium-based metal-organic framework materials in the prior art, and provides a preparation method and application of an ammonia-adsorbing titanium-based metal-organic framework material. By adjusting the synthesis temperature of the titanium-based metal-organic framework material, its ammonia adsorption performance can be significantly improved, and it can be used in filters and ammonia storage and transportation materials.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing an ammonia adsorbed titanium-based metal organic framework material, comprising the following steps: (1) mixing the organic ligand and the organic solvent and stirring them uniformly; (2) adding a titanium source to the solution obtained in step (1), and then performing a solvothermal reaction at 68 to 98° C. to obtain the ammonia-adsorbed titanium-based metal organic framework material.
[0007] In the prior art, when Ti-MOFs are prepared by solvent thermal method, the reaction temperature is usually around 150°C. The present invention has found through research that by controlling the synthesis temperature within the range of 68-98°C, the product will not become uniformly crystalline, and at the same time, it has pores below 10nm and 10-50nm, which can significantly improve the ammonia adsorption performance of the obtained Ti-MOFs, so that it can be used in deodorization filters or ammonia storage and transportation materials. In addition, low-temperature preparation also helps to reduce carbon dioxide emissions during the preparation process, reduce the risk of reaction and improve production efficiency.
[0008] Preferably, the solvent thermal reaction time in step (2) is 60 to 80 hours.
[0009] Preferably, the organic ligand is 2-aminoterephthalic acid, and the titanium source is tetrabutyl titanate.
[0010] Preferably, the addition ratio of the organic ligand and the titanium source is 1 g: 1 to 1.5 mL.
[0011] Preferably, the organic solvent in step (1) is a mixed solvent of DMF and methanol.
[0012] Preferably, the volume ratio of DMF to methanol is 50:10-20.
[0013] Preferably, in step (1), the organic ligand is first added to DMF, stirred at 100-120° C. for 0.5-2 h, and then methanol is added, and stirring is continued for 0.5-2 h.
[0014] Preferably, after the solvothermal reaction in step (2), the product is washed with DMF and methanol in sequence, and then dried under reduced pressure at 90 to 110° C. to obtain the ammonia-adsorbing titanium-based metal-organic framework material.
[0015] Preferably, after drying under reduced pressure, the product is subjected to reflux extraction with methanol to remove impurities, and then dried under reduced pressure at 90-110° C. for 2-4 days to obtain the ammonia adsorbed titanium-based metal organic framework material; the reflux extraction temperature is 110-130° C., and the extraction time is 3-5 hours.
[0016] In a second aspect, the present invention provides an application of an ammonia-adsorbing titanium-based metal-organic framework material obtained by the above-mentioned preparation method in a deodorizing filter. Since the titanium-based metal-organic framework material obtained by the method of the present invention has good adsorption performance for ammonia, it is used in a deodorizing filter, and the filter can be used in places with high ammonia content (such as animal husbandry farms, etc.).
[0017] In a third aspect, the present invention provides an application of an ammonia-absorbing titanium-based metal-organic framework material obtained by the above-mentioned preparation method in ammonia storage and transportation materials. The titanium-based metal-organic framework material obtained by the method of the present invention is used in ammonia storage and transportation materials, and can absorb ammonia in a place rich in ammonia and then transport it to a place where ammonia is needed, which is convenient for ammonia storage and transportation.
[0018] Therefore, the present invention has the following beneficial effects: (1) Adjusting the synthesis temperature of titanium-based metal-organic framework materials can significantly improve their adsorption performance for ammonia; (2) Low temperature preparation helps reduce carbon dioxide emissions during the preparation process, lowers reaction risk and improves production efficiency; (3) The titanium-based metal organic framework material prepared in the present invention can be used in filters, so that the filters have better deodorization performance and can be used in places with high ammonia content (such as animal husbandry farms, etc.); (4) The titanium-based metal organic framework material prepared in the present invention can be used in ammonia storage and transportation materials, which facilitates the storage and transportation of gaseous materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a SEM image of the ammonia adsorbed titanium-based metal organic framework material obtained in Example 3.
[0020] Figure 2 This is the SEM image of the ammonia adsorbed titanium-based metal organic framework material obtained in Comparative Example 1.
[0021] Figure 3 This is the pore distribution diagram of the ammonia adsorbed titanium-based metal organic framework material obtained in Example 3.
[0022] Figure 4 This is the pore distribution diagram of the ammonia adsorbed titanium-based metal organic framework material obtained in Comparative Example 1.
[0023] Figure 5 This is the pore distribution diagram of the ammonia adsorbed titanium-based metal organic framework material obtained in Comparative Example 2.
[0024] Figure 6 This is the XRD diagram of the ammonia adsorbed titanium-based metal organic framework material obtained in Example 2.
[0025] Figure 7 This is the XRD diagram of the ammonia adsorbed titanium-based metal organic framework material obtained in Example 4.
[0026] Figure 8 This is the XRD diagram of the ammonia adsorbed titanium-based metal organic framework material obtained in Comparative Example 1.
[0027] Fig. 9This is the XRD pattern of the commercially available NH2-MIL-125 material in Comparative Example 4. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.
[0029] In the present invention, unless otherwise specified, all equipment and raw materials can be purchased from the market or are commonly used in the industry. The methods in the following embodiments, unless otherwise specified, are conventional methods in the art.
[0030] Overall embodiment: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) mixing the organic ligand and the organic solvent and stirring them uniformly; (2) adding a titanium source to the solution obtained in step (1), and then performing a solvothermal reaction at 68 to 98° C. to obtain the ammonia-adsorbed titanium-based metal organic framework material.
[0031] As a specific implementation manner, the solvent thermal reaction time in step (2) is 60 to 80 hours.
[0032] As a specific implementation, the organic ligand is 2-aminoterephthalic acid, and the titanium source is tetrabutyl titanate.
[0033] As a specific implementation manner, the addition ratio of the organic ligand and the titanium source is 1 g: 1 to 1.5 mL.
[0034] As a specific implementation manner, the organic solvent described in step (1) is a mixed solvent of DMF and methanol.
[0035] As a specific implementation manner, the volume ratio of DMF to methanol is 50:10-20.
[0036] As a specific implementation method, in step (1), the organic ligand is first added to DMF, stirred at 100-120° C. for 0.5-2 h, and then methanol is added, and stirring is continued for 0.5-2 h.
[0037] As a specific implementation, after the solvothermal reaction in step (2), the product is washed with DMF and methanol in sequence, and then dried under reduced pressure at 90 to 110° C. to obtain the ammonia adsorbed titanium-based metal organic framework material.
[0038] As a specific implementation method, after drying under reduced pressure, the product is refluxed and extracted with methanol to remove impurities, and then dried under reduced pressure at 90 to 110° C. for 2 to 4 days to obtain the ammonia adsorbed titanium-based metal organic framework material; the reflux extraction temperature is 110 to 130° C., and the extraction time is 3 to 5 hours.
[0039] Embodiment 1: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 110° C. for 1 hour; then add 14 mL of methanol, and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 68° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) placing the ammonia adsorbed titanium-based metal-organic framework material obtained in step (2) in a cylindrical filter paper, then placing it in a Soxhlet extractor, adding 50 g of methanol, and refluxing at 120° C. for 4 hours to remove impurities; placing the obtained product in a reduced pressure dryer and drying it at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal-organic framework material.
[0040] Embodiment 2: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 110° C. for 1 hour; then add 14 mL of methanol, and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 78° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) The ammonia adsorbed titanium-based metal organic framework material obtained in step (2) is placed in a cylindrical filter paper, and then placed in a Soxhlet extractor, 50 g of methanol is added, and refluxed at 120° C. for 4 hours to remove impurities; the obtained product is placed in a reduced pressure dryer and dried at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal organic framework material, and an XRD analysis is performed on it. The results are as follows: Figure 6 as shown in .
[0041] Embodiment 3: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 110° C. for 1 hour; then add 14 mL of methanol, and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 88° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) The ammonia adsorbed titanium-based metal-organic framework material obtained in step (2) is placed in a cylindrical filter paper, and then placed in a Soxhlet extractor, 50 g of methanol is added, and refluxed at 120° C. for 4 hours to remove impurities; the obtained product is placed in a reduced pressure dryer and dried at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal-organic framework material, which is subjected to SEM testing. The results are as follows: Figure 1 As shown in; the pore distribution was measured, the results are as follows Figure 3 as shown in .
[0042] Embodiment 4: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 110° C. for 1 hour; then add 14 mL of methanol, and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 98° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) The ammonia adsorbed titanium-based metal organic framework material obtained in step (2) is placed in a cylindrical filter paper, and then placed in a Soxhlet extractor, 50 g of methanol is added, and refluxed at 120° C. for 4 hours to remove impurities; the obtained product is placed in a reduced pressure dryer and dried at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal organic framework material, and an XRD analysis is performed on it. The results are as follows: Figure 7 as shown in .
[0043] Comparative Example 1: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 110° C. for 1 hour; then add 14 mL of methanol, and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 108° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) The ammonia adsorbed titanium-based metal-organic framework material obtained in step (2) is placed in a cylindrical filter paper, and then placed in a Soxhlet extractor, 50 g of methanol is added, and refluxed at 120° C. for 4 hours to remove impurities; the obtained product is placed in a reduced pressure dryer and dried at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal-organic framework material, which is subjected to SEM testing. The results are as follows: Figure 2 As shown in; the pore distribution was measured, the results are as follows Figure 4 As shown in; and XRD analysis was performed on it, the results are as follows Figure 8 as shown in .
[0044] Comparative Example 2: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 110° C. for 1 hour; then add 14 mL of methanol, and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 118° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) The ammonia adsorbed titanium-based metal-organic framework material obtained in step (2) is placed in a cylindrical filter paper, which is then placed in a Soxhlet extractor, 50 g of methanol is added, and the mixture is refluxed at 120° C. for 4 hours to remove impurities; the obtained product is placed in a reduced pressure dryer and dried at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal-organic framework material, and its pore distribution is measured. The results are as follows: Figure 5 as shown in .
[0045] Comparative Example 3: A method for preparing an ammonia-adsorbed titanium-based metal-organic framework material comprises the following steps: (1) Add 3.64 g of 2-aminoterephthalic acid to DMF (50 mL), and stir at 50° C. for 1 hour; then add 14 mL of methanol and continue stirring for 1 hour; (2) adding 4.2 mL of tetrabutyl titanate to the solution obtained in step (1), stirring the solvent thermal reaction at 88° C. for 72 hours; filtering and separating the precipitated solid, washing it with 50 g of DMF, then washing it with 50 g of methanol, and then drying it under reduced pressure at 100° C. to obtain an ammonia-adsorbed titanium-based metal-organic framework material; (3) placing the ammonia adsorbed titanium-based metal-organic framework material obtained in step (2) in a cylindrical filter paper, then placing it in a Soxhlet extractor, adding 50 g of methanol, and refluxing at 120° C. for 4 hours to remove impurities; placing the obtained product in a reduced pressure dryer and drying it at 100° C. for three days to obtain an activated ammonia adsorbed titanium-based metal-organic framework material.
[0046] Comparative Example 4: The commercially available titanium-based metal organic framework material NH2-MIL-125 (AYRSORB from strem) was subjected to XRD analysis, and the results are as follows: Fig. 9 as shown in .
[0047] Comparative Example 5: Commercially available activated carbon T-BFU.
[0048] The ammonia adsorption performance of the activated ammonia adsorption titanium-based metal organic framework materials prepared in the above examples and comparative examples was tested, and the results are shown in Table 1.
[0049] Among them, the test method for ammonia adsorption performance is: put 0.1g of activated ammonia-adsorbed titanium-based metal-organic framework material sample into a glass tube with an inner diameter of 15mm and equipped with a glass filter, and pass air containing 32ppm ammonia into the tube at a flow rate of 0.27L / min; use a detection tube (Gastec detection tube 3L) to measure the ammonia concentration in the air on the outlet side once an hour, and calculate the adsorption amount of ammonia by the ammonia-adsorbed titanium-based metal-organic framework material.
[0050] Table 1: Ammonia adsorption test results. serial number Synthesis temperature (℃) Ammonia adsorption capacity (mg / g) Example 1 68 20 Example 2 78 27 Example 3 88 22 Example 4 98 18 Comparative Example 1 108 6 Comparative Example 2 118 12 Comparative Example 3 50 11 Comparative Example 4 - 7 Comparative Example 5 - 9
[0051] from Figures 1 to 9 It can be seen that the titanium-based metal organic framework material prepared by the low temperature synthesis method of the present invention in Example 3 will not become a uniform crystal ( Figure 1 ), while the titanium-based metal organic framework material prepared at a higher temperature in Comparative Example 1 is uniformly crystalline ( Figure 2 The titanium-based metal organic framework material prepared by the low temperature synthesis method of the present invention has pores of less than 10 nm and 10 to 50 nm ( Figure 3 ), while the pores of the titanium-based metal organic framework material prepared at 108°C in Comparative Example 1 are basically concentrated below 10 nm ( Figure 4 ), in Comparative Example 2, the synthesis temperature was further increased, and the pores of the titanium-based metal organic framework material prepared at 118°C were basically no more than 20nm ( Figure 5 ). In addition, the XRD patterns of the titanium-based metal organic framework materials prepared by the low temperature synthesis method of the present invention in Examples 2 and 4 are ( Figure 6 , Figure 7 ) and the XRD pattern of the commercially available titanium-based metal organic framework material NH2-MIL-125 in Comparative Example 4 ( Fig. 9 ) are also significantly different. In comparative example 1, the synthesis temperature was increased to 108°C, and the XRD pattern of the titanium-based metal organic framework material was obtained ( Figure 8 ) is compared with the XRD pattern of the commercially available titanium-based metal organic framework material NH2-MIL-125 in Comparative Example 4 ( Fig. 9 )resemblance.
[0052] Combined with the test data in Table 1, it can be seen that the titanium-based metal organic framework materials prepared by the low-temperature synthesis method of the present invention in Examples 1 to 4 have high ammonia adsorption capacity, while the synthesis temperature in Comparative Examples 1 and 2 is increased to 108°C and 118°C, and the ammonia adsorption effect of the obtained titanium-based metal organic framework materials is significantly reduced compared with the examples. In Comparative Example 3, the reaction temperature is too low, lower than the lower limit of the temperature range of the present invention, so the MOF structure cannot be formed, and the ammonia adsorption performance of the obtained product is also significantly reduced compared with the examples.
[0053] In addition, the commercially available titanium-based metal organic framework material NH2-MIL-125 in Comparative Example 4 and the commercially available activated carbon material in Comparative Example 5 The ammonia adsorption performance of T-BFU cannot reach the level of the examples of the present invention, which indicates that the present invention adopts a low-temperature synthesis method to significantly improve the ammonia adsorption performance of titanium-based metal organic framework materials.
[0054] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing an ammonia adsorbed titanium-based metal organic framework material, characterized in that it comprises: Follow these steps: (1) Mixing the organic ligand and the organic solvent and stirring them uniformly; (2) Adding a titanium source to the solution obtained in step (1), and then performing a solvothermal reaction at 68-98° C. to obtain the ammonia-adsorbed titanium-based metal organic framework material.
2. The method for preparing the ammonia adsorbed titanium-based metal organic framework material according to claim 1, characterized in that: The solvent thermal reaction time in step (2) is 60 to 80 hours.
3. The method for preparing the ammonia adsorbed titanium-based metal organic framework material according to claim 1, characterized in that: The organic ligand is 2-aminoterephthalic acid, and the titanium source is tetrabutyl titanate.
4. The method for preparing the ammonia adsorbed titanium-based metal organic framework material according to claim 3, characterized in that: The addition ratio of organic ligand and titanium source is 1g:1~1.5mL.
5. The method for preparing the ammonia adsorbed titanium-based metal organic framework material according to claim 1 or 3, characterized in that: The organic solvent in step (1) is a mixed solvent of DMF and methanol; the volume ratio of DMF to methanol is 50:10-20.
6. The method for preparing the ammonia adsorbed titanium-based metal organic framework material according to claim 5, characterized in that: In step (1), the organic ligand is first added to DMF, stirred at 100-120°C for 0.5-2h, and then methanol is added, and stirring is continued for 0.5-2h.
7. The method for preparing ammonia adsorbed titanium-based metal organic framework material according to claim 1, characterized in that: After the solvent thermal reaction in step (2), the product is washed with DMF and methanol in sequence, and then dried under reduced pressure at 90-110° C. to obtain the ammonia adsorbed titanium-based metal organic framework material.
8. The method for preparing ammonia adsorbed titanium-based metal organic framework material according to claim 7, characterized in that: After drying under reduced pressure, the product is refluxed and extracted with methanol to remove impurities, and then dried under reduced pressure at 90-110° C. for 2-4 days to obtain the ammonia adsorbed titanium-based metal organic framework material; the reflux extraction temperature is 110-130° C., and the extraction time is 3-5 hours.
9. Use of an ammonia adsorbing titanium-based metal organic framework material obtained by the preparation method according to any one of claims 1 to 8 in a deodorizing filter.
10. Use of an ammonia adsorbing titanium-based metal organic framework material obtained by the preparation method according to any one of claims 1 to 8 in ammonia storage and transportation materials.
